The Effect Of Obesity On Oxidative Stress And Some Selected Antioxidants Among Nigerian Obese Diabetics And Hypertensive. - Blessing, Idonije O; Abraham, Onigbinde O; George, Eidangbe O (Asian Journal of Medical Research, 2017)
Objective: Co-existence of diabetes and hypertension is known to aggravate cardiovascular complications. Of interest is what impact obesity has considering its prevalence in the general population and the public health implication? Hence, this study investigated the effect of obesity on diabetes and hypertension vis-a-vis oxidative stress and some antioxidant status. Methods: The study population comprised of 264 subjects; obese hypertensive (OH; n=59), obese diabetes (OD; n=59), obese diabetes and hypertensive (ODH; n=41), obese non diabetes and non hypertensive (ONDH; 45) and non obese non diabetes and non hypertensive (NONDH; control; n=60). There ages, blood pressure, fasting blood glucose and body mass index were determined using standard techniques while Malondialdehyde (MDA) levels was used to determine oxidative stress status and Vitamins A and E with Nitric oxide (NO) were used for the assessment of the antioxidants status and these were analyzed via standard laboratory procedures. Results: The control were younger, however the age difference between groups were not significant. BMI was not significantly different when test groups were compared but with control, the difference was significant. The mean blood pressure for the control was significantly lower than those of the OH, ODH and OD but not significantly different from that of ONDH. Also, fasting blood glucose was significantly higher amongst the ODH and OD groups compared to the OH, NODH and control groups. Compared with the control, marker of oxidative stress (MDA) was lower although not significantly different from those of ODH, OD, OH and ONDH. Variations were observed with biomarkers of antioxidants status studied and these were observed to be significant in terms of vitamin A in the ODH, OD and OH groups compared to the ONDH and control groups. However, the vitamin E level for the control was not significantly different from those of ONDH and OD but significantly different from those of the OH and ODH groups. Also, nitric oxide levels among the groups were not significantly different. Conclusion: Obesity is an oxidatively stressed condition which worsens with diabetes and or hypertension complicating it but interestingly these complications increased the levels of antioxidants (vitamin A and NO) studied. Keywords: Obesity, Oxidative stress, Antioxidant, Diabetes, Hypertension.